2011
DOI: 10.1007/s11669-011-9872-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Solubility Characteristic of the Antisolvent Crystallization of RDX

Abstract: The laser monitoring observation technique is proposed to measure the solubility and supersolubility of RDX in different proportion and temperature for the antisolvent crystallization. Experimental determination of the solubilities curve and the metastable zone widths (MSZWs) are presented. Knowledge of the solubility curve and the stability of the solution in the vicinity of the equilibrium point, as indicated by the MSZW, is essential to the successful development, optimization, and scale-up of a crystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The solubilities of 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline in methanol, acetone, ethyl acetate, chloroform, and 1,2-dichloroethane between 285 K and 333.75 K were measured by experiments; all of the data are presented in Tables and . The temperature dependence of 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline solubility in pure solvents is described by the modified Apelblat equation, , which is a semiempirical equation derived from the Clausius–Clapeyron equation. ln nobreak0em.25em⁡ x = A + B / ( T / K ) + C nobreak0em0.25em⁡ ln ( T / K ) where A , B , and C are dimensionless parameters, which are also shown in Table together with ε, σ; T is the absolute temperature; and x is the experimental mole fraction solubility of the 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubilities of 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline in methanol, acetone, ethyl acetate, chloroform, and 1,2-dichloroethane between 285 K and 333.75 K were measured by experiments; all of the data are presented in Tables and . The temperature dependence of 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline solubility in pure solvents is described by the modified Apelblat equation, , which is a semiempirical equation derived from the Clausius–Clapeyron equation. ln nobreak0em.25em⁡ x = A + B / ( T / K ) + C nobreak0em0.25em⁡ ln ( T / K ) where A , B , and C are dimensionless parameters, which are also shown in Table together with ε, σ; T is the absolute temperature; and x is the experimental mole fraction solubility of the 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline.…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge of the thermophysical properties is important not only for the design of separation, extraction, and absorption processes but also to take decisions regarding the influences of solvents on reaction rates and drug design and formulation development in the pharmaceutical industry. , Widely used in medicine, dyes, and printing industries, the thermophysical properties of 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline, such as the solubility, density, activity, and coefficient, are essential data for product development and process design in industrial production, especially since their solubilities are of crucial importance in the determination of proper solvents and the development and operation of crystallization processes. , Therefore, it is necessary to determine the solubility data of 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline in different solvents. To our knowledge, this is the first time the solubilities of 3-methoxy- N -phenylaniline and 3-(methylthio)- N -phenylaniline are reported.…”
Section: Introductionmentioning
confidence: 99%
“…RDX is widely used in propellants 41,42 and polymer bonded explosives (PBXs). 43,44 Dissolving thermodynamic properties of RDX in varying solvents have been investigated by different means, including FBRM, 45 the laser monitoring observation technique, 46 the static equilibrium method 47,48 and the evaporation of solvent in the saturated solution method. 49 The solubility of RDX in different pure solvents is shown in Figure 1a,b, and it is clear that the solubility of RDX is positively dependent on temperature.…”
Section: Dissolution Thermodynamics In Organic Solvent Systemsmentioning
confidence: 99%
“…The MSZW of RDX in ACE/ water binary solvent was studied, and the effect of antisolvent addition rate on MSZW was analyzed, and then its impact on crystal size was further explained. 46 The higher rate of antisolvent (water) addition leads to higher local supersaturation and narrower MSZW, so it is easier to form more crystal nuclei, which is not favorable for the growth of crystals, resulting in smaller particle sizes. The molecular dynamics simulation method 48 was adopted to research the dissolution mechanism of RDX in an ethyl acetate (EA)/water binary system, where the solubility parameters of RDX in this binary solvent were calculated, and the results demonstrated that the solubility of RDX would be increased with the mole fraction of water in this binary system, which is completely opposite to the situations of HMX and CL-20.…”
Section: Dissolution Thermodynamics In Organic Solvent Systemsmentioning
confidence: 99%
“…Although the widely used way to measure the concentration of the saturated solution is by gravimetric method which is similar to those described in the previous works, veramoss has a tendency to cake or clump at the evaporation temperature of the solvent, leading to a significant error to the result of experimental solubility. Compared to other methods of measured solubility, the dynamic method more readily and much faster produces solubility values. The experimental solubility data were correlated with the Apelblat model, , van’t Hoff model, and CNIBS/R model, which describe the relationship between solubility and temperature, as well as the relationship between solubility and solvent composition. The thermodynamic parameters (dissolving enthalpy, dissolving entropy, and Gibbs free energy) were calculated based on the Wilson equation and experimental solubility data; these experimental data can be used in the crystallization and purification of veramoss.…”
Section: Introductionmentioning
confidence: 99%